Inhomogeneous Diophantine approximation over fields of formal power series - Bugeaud, Yann; Singhal, L.; Zhang, Zhenliang (MATHEMATICA SCANDINAVICA, 2020)
We prove a sharp analogue of Minkowski's inhomogeneous approximation theorem over fields of power series $\mathbb {F}_q((T^{-1}))$. Furthermore, we study the approximation to a given point $\underline {y}$ in $\mathbb {F}_q((T^{-1}))^2$ by the $SL_2(\mathbb {F}_q[T])$-orbit of a given point $\underline {x}$ in $\mathbb {F}_q((T^{-1}))^2$.